FACTOR AFFECTING COMMUNITY AWARENESS AND PARTICIPATION IN WASTE MANAGEMENT, CASE STUDY BANG RAK NOI SUBDISTRICT COMMUNITY, MUEANG DISTRICT, NONTHABURI PROVINCE - Kongyoungyune, Rungradit; Kongyoungyune, Pinavet; Sawatdikumthon, Thakon (Journal of Educational Review Faculty of Education in MCU, 2024)
The research article aimed to study 1) the level of awareness and community participation in waste management among the people of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province, 2) the relationship between community awareness and participation in the waste management of the people of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province, 3) factor affecting awareness and participation of the people in the management of solid waste in the community. This research was a quantitative research using a questionnaire research instrument. The population was people in the community living in the Bang Rak Noi Subdistrict Administrative Organization area, numbering 30,785 people, using as a sample of 395 people. The results of the research found that; 1) Level of community awareness and participation in managing waste of the people of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province in all aspects were at a moderate level. 2) Relationship between community awareness and participation in managing waste of the people of Bang Rak Noi Subdistrict, Mueang District, Nonthaburi Province in overall, there was a statistically significant high positive relationship (r = 0.714, p < 0.01), and all aspects of the awareness factor and participation factor had a significantly high positive relationship with statistical significance at 0.01. For each aspect, it was found that the aspect with the highest relationship was creating awareness in the community and participating in community waste management, there was a positive relationship with a high level of statistical significance (r = 0.742, p < 0.01), followed by the aspect of creating awareness in the community and the aspect of supporting the community waste management project which had a positive relationship at high level of statistical significance (r = 0.668, p < 0.01). The side with the least relationship was the aspect of household waste separation and the evaluation aspect of community waste management projects had a low and statistically significant positive relationship (r = 0.345, p < 0.01). 3) The awareness factor had a statistically significant positive influence on the participation factor, the overall standard multiple regression coefficient was equal to 0.714, with statistical significance at the 0.01 level, and the overall quadratic multiple correlation coefficient (R2) was equal to 0.510, meaning that 51.10 percent of the variance in the participation factor could be predicted by cognitive factors.